Molecular screening for bacterial pathogens in ticks (Ixodes ricinus) collected on migratory birds captured in northern Italy - Pajoro, Massimo; Pistone, Dario; Varotto Boccazzi, Ilaria; Mereghetti, Valeria; Bandi, Claudio; Fabbi, Massimo; Scattorin, Francesco; Sassera, Davide; Montagna, Matteo (Folia parasitologica, 2018)
Migratory birds have an important role in transporting ticks and associated tick-borne pathogens over long distances. In this study, 2,793 migratory birds were captured by nets in a ringing station, located in northern Italy, and checked for the presence of ticks. Two-hundred and fifty-one ticks were identified as nymphs and larvae of Ixodes ricinus (Linnaeus, 1758) and they were PCR-screened for the presence of bacteria belonging to Borrelia burgdorferi sensu lato, Rickettsia spp., Francisella tularensis and Coxiella burnetii. Four species of Borrelia (B. garinii, B. afzelii, B. valaisiana and B. lusitaniae) and three species of Rickettsia (R. monacensis, R. helvetica and Candidatus Rickettsia mendelii) were detected in 74 (30%) and 25 (10%) respectively out of 251 ticks examined. Co-infection with Borrelia spp. and Rickettsia spp. in the same tick sample was encountered in 7 (7%) out of the 99 infected ticks. We report for the first time the presence of Candidatus Rickettsia mendelii in I. ricinus collected on birds in Italy. This study, besides confirming the role of birds in dispersal of I. ricinus, highlights an important route by which tick-borne pathogens might spread across different countries and from natural environments towards urbanised areas.
Keywords: Animals; molecular characterisation; Rickettsia; Animal Migration; Prevalence; klíště; Songbirds; infestace klíšťaty; nymfa; zpěvní ptáci; Candidatus Rickettsia mendelii; Italy; Migratory birds; nemoci ptáků; Itálie; Borrelia spp.; Nymph; Bird Diseases; prevalence; Bacteria; migrace zvířat; Larva; zvířata; Tick Infestations; tick-borne pathogens; Ixodes; larva; Borrelia